Use of Scenario-Based Nominal Group Techniques to Evaluate System Functions: Examples from the USA & Sweden - Rachael Piltch-Loeb; Anna Ekström; Rachel Neilsen (Proceedings, 2021)
The nominal group technique (NGT) was developed in the 1970s as a structured brainstorming and multi-stage consensus-building process to solicit feedback from a group of stakeholders on a given topic. The approach was intended as an evaluation method to provide semi-quantitative rank-ordered feedback from group participants. This lecture presents a variation of this technique created by the Harvard team, namely “scenario-based NGT”. The format proposed includes elements of tabletop exercises (scenario with a timeline and discussion phase) as well as elements of traditional NGTs (silent brainstorming and ranking). The technique we developed was based on a case-study approach (“scenario”) which we then tested in two countries (USA and Sweden) with existing P/CVE initiatives at different stages of development. We conducted scenario-based NGT sessions in both locations and then systematically analyzed the results using iterative qualitative coding based on a common framework. Results were analyzed to achieve consensus on the most common system-level challenges and system-level functions, necessary to overcome those challenges, in each location.